Universal hearing screening of newborn to detect hearing loss and aid in early intervention: multicentre study - Yenamandra, Kamal K.; Sahu, Pankaj K.; Kumar, Anil; Rai, N.; Thakur, Pankaj K. (International Journal of Contemporary Pediatrics, 2018)
Background: Significant hearing loss is one of the most common major abnormalities present at birth. Screening for hearing loss in new-born is based on two concepts. First, a critical period exists for optimal language skills to develop, and Second, earlier intervention produces better outcomes. Methods: A two-stage screening protocol, in which new-born are screened first with two staged Transient Evoked Oto-acoustic Emissions TEOAE, using handheld TEOAE device, followed by confirmation with Auditory Brainstem Response (ABR). The objective was to study the incidence of hearing impairment in “healthy” and “high risk‟ newborns. A prospective observational study of hearing impairment screening was conducted on 4400 newborns, the study was done as a multi-centre study in 3 different hospitals during January 10 - December 14. Results: 4400 new born, born during the study period were screened, which included 4162(94.7%) healthy neonates and remaining 238(5.3%) high risk neonates. 24 newborn among the cohort of 4400, had hearing impairment confirmed by ABR. The overall incidence of hearing impairment is 5.45/ 1000 screened with 95 % confidence interval between 4.28-11.6. Incidence of hearing impairment in the "no risk‟ group was 2.4/1000 with 95 % confidence interval between 2.01- 4.66. Whereas incidence of 58.8/1000 with 95 % confidence interval is between 1.96-10.32 was seen in "at risk‟ group. Also, this study shows Universal hearing screening of newborns with a two staged screening protocol using TEOAE followed by confirmation with ABR is not only cost effective for detection of hearing loss but also aids in early intervention. Conclusions: The incidence of hearing impairment in our study (5.45 per 1000) is much higher than results shown in previous studies and national average of 4/1000.